Características bioquímicas e estruturais de músculus de ema (Rhea americana): implicações sensoriais e nutricionais - Filgueras, Renata Schmidt (2010)
Biochemical characteristics and oxidative stability during chilling and frozen were studied in M. Gastrocnemius pars interna (GN) and M. Iliofiburalis (IF) of rhea americana. The histochemical and morphometrical study was also conducted to determine fibre types and structural and ultrastructural differences between GN and IF muscles of rhea. Finally, the in vitro protein digestibility and the nutritional value of proteins were also investigated after storage/ageing and cooking in GN muscle. The ultimate pH was similar in both muscles, but the glycolytic potential (GP) was significantly higher in IF than in GN muscle. Under chilling (4 °C) and air-packaging rhea muscles exhibited differences in their stability. In particular, the IF muscle presented high colour instability and high lipid and protein oxidations after 5 days of air-packaged storage. Under chilling (4 °C) and vacuum-packaging both muscles were highly stables during 28 days and did not present evidences of oxidation. Under frozen (-20 °C) GN muscle was perfectly stable during 180 days, but IF muscle presented evidences of lipid and myoglobin oxidation after 90 days of storage. The fatty acid composition, higher lipid content and the higher myoglobin concentration in IF than in GN muscle could partially explain the instability of IF muscle during air-packaging, but the high residual glycogen observed in biochemical analysis also seemed to be involved in the occurrence of the oxidative process. The histochemical analysis of rhea limb muscles demonstrated the presence of only one type of fibres in both GN and IF muscles, i.e. fast-twitch oxidative and glycolytic (FOG) fibres. The homogeneity of fibres was evident after m-ATPase, SDH and glycogen staining reactions. In addition, the ultrastructural observation of rhea myofibrils showed contracted and stretched areas, as well as abundant glycogen and numerous mitochondria, mainly in IF muscle. Finally, the study of protein nutritional value and protein rate of digestion indicated that storage/ageing had less impact than cooking on protein oxidation and aggregation. After cooking (100 °C, 30 min) the aggregates increased 400% and the content of aromatic amino acids decreased. The nutritional value of proteins was affected by cooking, as demonstrated by the decrease of pepsin activity rate. However, trypsin chymotrypsin activities were stable after heat treatment.